Pengaruh Struktur Modal Dan Intellectual Capital Terhadap Kinerja Keuangan Dengan Ukuran Perusahaan Sebagai Variabel Intervening Pada Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2024 - Tari Oktavani (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to examine the effect of capital structure and intellectual capital on financial performance with firm size as an intervening variable in banking companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Banking financial performance is a crucial indicator in assessing the effectiveness of resource management and the resilience of the financial sector, particularly during the post-pandemic recovery period. The independent variables in this study are capital structure and intellectual capital, the dependent variable is financial performance, and firm size acts as an intervening variable. The population consists of 47 banking companies listed on the Indonesia Stock Exchange. The sampling technique uses purposive sampling based on predetermined criteria, resulting in 30 companies observed over five years. The study employs secondary data derived from annual financial reports. Data analysis methods include multiple linear regression and path analysis supported by SPSS version 26. Classical assumption tests were conducted to ensure the validity and reliability of the regression model. The results indicate that capital structure has a significant effect on firm size, while intellectual capital does not significantly affect firm size. Capital structure does not have a significant direct effect on financial performance, whereas intellectual capital has a significant positive effect on financial performance. Firm size significantly influences financial performance. Path analysis shows that capital structure has a significant indirect effect on financial performance through firm size as an intervening variable, while intellectual capital does not show a significant indirect effect through firm size. These findings imply that capital policy and intellectual resource management contribute differently to improving banking financial performance.